Edukasi Kesehatan Mental dalam Upaya Preventif Gangguan Psikologis pada Remaja di SMKN 3 Raha - Sugarni, Mika; Wulan, Wulan; Wulandari, Bety Anisa; Sumi, Susi Sastika (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Health is a basic need for everyone. Adolescent mental health is an increasingly pressing global issue. Teenagers are currently vulnerable to various mental health issues, such as depression, anxiety, eating disorders, and even suicide attempts. The purpose of this community service is to provide information on preventative measures for adolescents who feel they have mental health problems or disorders. The target group for this community service is adolescents aged 14-17. The community service program lasts one day. The approach used is socialization and outreach activities. The activity is carried out offline with lectures during the presentation of the material, a question and answer session to assess participants' understanding, a discussion that includes a dialogue addressing mental health issues and psychological disorders in adolescents, and a video displaying several images as evidence of the incident.